2016
DOI: 10.1103/physrevb.93.161112
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of nonequivalent Fermi-arc states of opposite surfaces in the noncentrosymmetric Weyl semimetal NbP

Abstract: We have performed high-resolution angle-resolved photoemission spectroscopy (ARPES) on noncentrosymmetric Weyl semimetal candidate NbP, and determined the electronic states of both Nband P-terminated surfaces corresponding to the "opposite" surfaces of a polar crystal. We revealed a drastic difference in the Fermi-surface topology between the opposite surfaces, whereas the Fermi arcs on both surfaces are likely terminated at the surface projection of the same bulk Weyl nodes. Comparison of the ARPES data with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
111
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 40 publications
9
111
0
Order By: Relevance
“…Our results for TaP and NbP reveal a universal evolution of the Fermi arc surface states, and demonstrate that these states disperse over a much larger energy range, compared to the energy range of the existence of Weyl fermion quasiparticles. For this reason, Fermi arcs can be observed in compounds such as NbP [40,41], even when there are no Weyl fermion quasiparticles and associated magnetotransport phenomena [45,46].…”
Section: Pagementioning
confidence: 99%
See 2 more Smart Citations
“…Our results for TaP and NbP reveal a universal evolution of the Fermi arc surface states, and demonstrate that these states disperse over a much larger energy range, compared to the energy range of the existence of Weyl fermion quasiparticles. For this reason, Fermi arcs can be observed in compounds such as NbP [40,41], even when there are no Weyl fermion quasiparticles and associated magnetotransport phenomena [45,46].…”
Section: Pagementioning
confidence: 99%
“…On the other hand, although the Fermi arcs, which are one of the spectroscopic hallmarks of a WSM, are observed in all members of the transition-metal monopnictide family at both pnictogen- [34,[36][37][38][39][40] and metalterminated [35,41] surfaces, the magnetotransport behaviors related to the chiral anomaly effect are distinct among the different compounds. The negative longitudinal MR, which has a maximum value of -30% at ~6 T in TaAs [42] and as large as -3000% at 9T in TaP without any sign of saturation [43,44], has never been observed in NbP [45,46].…”
Section: Pagementioning
confidence: 99%
See 1 more Smart Citation
“…In non-centrosymmetric Weyl semimetals, different patterns of Fermi arcs on the top and bottom surfaces are theoretically expected [36,37]. Indeed, an ARPES study on NbP [38] revealed the nonequivalent forms of Fermi arcs on respective surfaces, that are terminated at the same 2D projected bulk Weyl nodes. Also for MoTe2, the difference of the surface states and Fermi arcs for both terminations are discussed in comparison with calculations [22,27].…”
mentioning
confidence: 99%
“…The existence of three-dimensional (3D) Dirac semimetals was first confirmed by angle-resolved photoemission spectroscopy (ARPES) of Cd 3 As 2 [9, 10] and Na 3 Bi [11], where the VB and CB contact each other at the point (Dirac point) protected by rotational symmetry of the crystal [12,13]. Recent ARPES studies on noncentrosymmetric transition-metal monopnictides [14][15][16][17] have clarified pairs of bulk Dirac-cone bands and Fermi-arc SSs, supporting their Weyl-semimetallic nature [18,19]. While the existence of Weyl semimetals with point nodes has been confirmed experimentally, the experimental studies of LNSMs with line nodes are relatively scarce [20][21][22][23] despite many theoretical predictions [24][25][26][27][28][29][30].…”
mentioning
confidence: 99%